(3EOGQI GdeMGaX GdGSJKeGQjIs - (3OQjO cGed(B, (3Bd THjHs ((3YeGf(B:s (3OGQ GdeSjQI(B,s, 2010)
(3ebOeI aj GdeMGaX GdGSJKeGQjI , fXQjI h GOGQI GdeMaXI GdGSJKeGQjI , GdYGFO h GdeNGWQ , bjGS GdYGFO h GdeNGWQ aj GdeMaXI , JMdjd HjFI GdGSJKeGQGJ aj GdeMaXI GdGSJKeGQjI , JMdjd GdeMaXI GdGSJKeGQjI , feGPL GdeMGaX GdGSJKeGQjI h CNjQG Jbjje COGA GdeMGaX GdGSJKeJQjI (B.s
(3eQGLY U(B.221((3GbJfGAGJ (B2014 10(3f(B)s
Keywords: (3GdGSJKeGQ GdeGdjs; (3GdGSJKeGQGJs; (3GdGbJUGO GdeGdjs